UMP master’s student won competition on research paper - Jolius, Gimbun
Faculty of Chemical and Natural Resources Engineering (FKKSA) master’s student Lee Hua Chyn was announced as the winner of a Research Paper Competition organised by the Institution of Engineers Malaysia (IEM)’s Chemical Engineering Technical Division (CETD).